Multiple Metamaterial Pattern Integration for Polarization Selective Photodetector Applications. (11th January 2018) - Shemelya, Corey; Pfiester, Nicole A.; DeMeo, Dante; Rotter, Thomas; Balakrishnan, Ganesh; Vandervelde, Thomas E.
ABSTRACT: Interest in active metamaterial (MM) devices has recently increased due to their potential for tunable, switchable, and scalable optical responses. More specifically, a dynamic, on-chip MM polarizer has applications ranging from material characterization to sensing without the need for cumbersome external filters. This work demonstrates efforts to optimize MM devices for dynamic polarization filtering by combining elements from split-ring resonators, wire-pairs, and fishnet patterns. The polarization grid has been designed to operate under an applied voltage with simulated on/off ratios of 75% and dynamic polarization selectivity of 70%. Samples have been fabricated using epitaxial GaAs on sapphire with various n-type doping concentrations to approximate electrical tuning.